Home > Subjects > Mathematics > Level 2 > 2.6 Algebra > Subject content > Expanding three brackets

- Subject: Mathematics
- AS: 91261
- Level: 2
- Credits: 4
- External

## Mathematics 2.6 Apply algebraic methods in solving problems

### Expanding three brackets

Example (x + 5)(x + 2)(x – 3) = (x + 5)(x^{2}– 3x + 2x – 6) Multiply out the second pair of brackets = (x + 5)(x^{2}– x – 6) –3x + 2x = –x = x^{3}– x^{2}– 6x + 5x^{2}– 5x – 30 Multiply all terms in second bracket by x and then everything in second bracket by 5 = x^{3}+ 4x^{2}– 11x – 30 Add the x^{2}terms together: – x^{2}+ 5x^{2}= 4x^{2}and the x terms together: – 6x – 5x = –11x